(untitled) (JURNAL ADMINISTRASI PUBLIK, 2018)
In the effort to overcome poverty various ways have been done by the government through Social assistance programs and One of the programs is the Family Hope Program. The hope family program is a social protection program through the provision of cash assistance to very poor families by fulfilling the required requirements related to efforts to improve the quality of human resources, namely education and health. As for the purpose of this research was to determine how the Implementation Of Hope Family Program In Pasan District Southeast Minahasa Regency. The research method used in this study is qualitative research method. Informants in the study are people who can provide information about the situation and condition of the research background. The focus of research is communication, resources, disposition and bureaucratic structure. Technique of collecting data through observation / direct observation kelokasi research, do interview, and documentation. The results showed that the implementation of hope family program in Pasan District of South Minahasa Regency has not been implemented well. The lack of socialization to the participants of the hope family program and resources in the mentoring process has not been well done into the implementation of the family hope program appropriately. Keywords : Implementation, Program, Family Hopes